FRI0019 MRI INFLAMMATION, DISEASE ACTIVITY AND FUNCTIONAL IMPAIRMENT ARE MORE EFFECTIVELY REDUCED BY ESCALATION TO BIOLOGICS COMPARED TO CSDMARD-ESCALATION IN RHEUMATOID ARTHRITIS PATIENTS IN CLINICAL REMISSION FOLLOWING A TREAT-TO-TARGET STRATEGY: SECONDARY ANALYSES OF THE IMAGINE-RA TRIAL. (2nd June 2020) - Møller-Bisgaard, S.; Hørslev-Petersen, K.; Ejbjerg, B.; Hetland, M. L.; Christensen, R.; Ørnbjerg, L.; Glinatsi, D.; Møllenbach Møller, J.; Boesen, M.; Stengaard-Pedersen, K.; Rintek Madsen, O.; Jensen, B.; et al.
Abstract : Background: The effect of different treatment escalations on MRI inflammation in rheumatoid arthritis (RA) patients following an MRI treat-to-target (T2T) strategy has not previously been investigated. Objectives: To compare the effect of different treatment escalations on MRI inflammation, physical function and disease activity in RA patients in clinical remission, following an MRI T2T strategy. Methods: One hundred RA patients in clinical remission (DAS28-CRP<3.2 and no swollen joints), on conventional synthetic (cs) DMARDs following an MRI T2T strategy targeting DAS28-CRP≤3.2, no swollen joints plus absence of MRI osteitis, were followed for 2 years with clinical and MRI (wrist and 2 nd -5 th MCP joints) evaluation every 4 months 1 . If target was not met, a predefined treatment escalation algorithm dictated: First: increase in csDMARDs (A), second: adding a TNF inhibitor (TNFi) (B), third and onwards: switch between biologics (C). If target was met, no change in baseline csDMARDs was done (D). Outcomes were assessed 4 months after treatment change. MRIs were evaluated with known chronology by one experienced reader. Repeated measures mixed linear models were used to express estimates of group differences on predefined co-primary outcomes (MRI osteitis, HAQ) and key secondary outcomes (MRI combined inflammation, Simplified Disease Activity Index (SDAI)). Results: Escalation to first TNFi (B) or to 2 nd or later biologic (C) compared to csDMARDs (A) was consistently more effective on all outcomes (e.g. in group B osteitis was reduced with 1.8 units more than A) (Table ). Unchanged (D) compared to escalation in csDMARD (A) treatment did not differ, except for HAQ-score. Escalation to a 2 nd or later biologics (C) compared to the first TNFi (B) was more effective suppressing MRI inflammation. Escalation to TNFi treatment (B) or to 2 nd or later biologic (C) compared to unchanged treatment (D) was more effective on all outcomes except from HAQ-score (no difference between groups). Conclusion: T2T-based treatment escalations to biologics compared to csDMARD-escalations more effectively improved MRI inflammation, physical function and disease activity. Further optimization of the treatment in RA patients in clinical remission may improve long-term outcomes. References: [1]Møller-Bisgaard et al. JAMA 2019 Disclosure of Interests: Signe Møller-Bisgaard Grant/research support from: AbbVie, Consultant of: BMS, Speakers bureau: BMS, Celgene, Pfizer, Kim Hørslev-Petersen: None declared, Bo Ejbjerg: None declared, Merete L. Hetland Grant/research support from: BMS, MSD, AbbVie, Roche, Novartis, Biogen and Pfizer, Consultant of: Eli Lilly, Speakers bureau: Orion Pharma, Biogen, Pfizer, CellTrion, Merck and Samsung Bioepis, Robin Christensen: None declared, Lykke Ørnbjerg: None declared, Daniel Glinatsi: None declared, Jakob Møllenbach Møller: None declared, Mikael Boesen Consultant of: AbbVie, AstraZeneca, Eli Lilly, Esaote, Glenmark, Novartis, Pfizer, UCB, Paid instructor for: IAG, Image Analysis Group, AbbVie, Eli Lilly, AstraZeneca, esaote, Glenmark, Novartis, Pfizer, UCB (scientific advisor)., Speakers bureau: Eli Lilly, Esaote, Novartis, Pfizer, UCB, Kristian Stengaard-Pedersen: None declared, Ole Rintek Madsen: None declared, Bente Jensen: None declared, Jan Villadsen: None declared, Ellen Margrethe Hauge: None declared, Philip Bennett: None declared, Oliver Hendricks: None declared, Karsten Asmussen: None declared, Marcin Kowalski: None declared, Hanne Merete Lindegaard: None declared, Henning Bliddal Grant/research support from: received research grant fra NOVO Nordic, Consultant of: consultant fee fra NOVO Nordic, Niels Steen Krogh: None declared, Torkell Ellingsen: None declared, Agnete Nielsen: None declared, Anne Grethe Jurik: None declared, Lone Balding: None declared, Henrik Thomsen: None declared, Mikkel Ǿstergaard Grant/research support from: AbbVie, Bristol-Myers Squibb, Celgene, Merck, and Novartis, Consultant of: AbbVie, Bristol-Myers Squibb, Boehringer Ingelheim, Celgene, Eli Lilly, Hospira, Janssen, Merck, Novartis, Novo Nordisk, Orion, Pfizer, Regeneron, Roche, Sandoz, Sanofi, and UCB, Speakers bureau: AbbVie, Bristol-Myers Squibb, Boehringer Ingelheim, Celgene, Eli Lilly, Hospira, Janssen, Merck, Novartis, Novo Nordisk, Orion, Pfizer, Regeneron, Roche, Sandoz, Sanofi, and UCB